Handbook of Tourism and Quality-of-Life Research II Enhancing the Lives of Tourists, Residents of Host Communities and Service Providers - Uysal, Muzaffer; Sirgy, M. Joseph (Cham : Springer International Publishing : Imprint: Springer, 2023)
The second volume of this handbook develops on and extends the discussion in the successful first volume, published in 2012. This is a timely addition to the literature, drawing on the momentum that quality of life (QOL) research in tourism has gained in the 21st century and on the boom in the tourism industry itself. It focuses on four areas of growth in QOL research in the recent past: (1) travelers/tourists, (2) host communities, (3) service providers, and (4) the role of technology. The handbook helps management of tourism firms and policy makers develop specific policies and programs to ensure the most positive impact of tourism on tourists, host communities, and service providers. The comprehensive coverage of topics in this handbook makes it a state-of-the-art reference. Academics interested in QOL research in travel and tourism, tourism practitioners interested in applying the science of QOL in the tourism industry, as well as policy makers involved in regulating the industry will view the handbook as indispensable source of recent research.
Prologue: An Introduction to QOL Research in Tourism -- Part I: QOL Research in Relation to Tourists -- Tourist consumption behavior and QOL, S. Kruger, C. Laesser, J. O'Leary, H. Oppewal, F. Dimanche -- Place and destination attachment and QOL, A. Graefe, D. Williams -- Subjective indicators of QOL and tourism, G. Godbey, S. McMahon, D. Kleiber -- Destination competitiveness from the perspectives of tourists and QOL, F. Meng -- Linking tourist satisfaction to happiness and QOL, S. Filep -- Phases of travel experiences, satisfaction - QOL, J. Neal, G. Richards -- Salient dimensions of tourist satisfaction and QOL, Y. Ekinci, S. Kruger, K. Weiermair -- Vacation experience and QOL of individuals (segmentation), S. Dolnicar, G. Jennings -- Impacts of the interaction between host and guest on QOL, R. Harrill, R. Li, E. Fredline -- Impacts of gaming on QOL of participants (visitors), K. Hsu, S. Baloglu -- Subjective wellbeing of QOL and medical tourism C. Cohen -- Subjective wellbeing of QOL and motivation, G. Dann -- QOL & medical tourism, T. Johnson -- Information technology in tourism and QOL, D. Fesenmaier, N. Christodulido -- Destination competitiveness from the perspectives of tourists and QOL, F. Meng -- Linking tourist satisfaction to happiness and QOL, S. Filep -- Part II: QOL Research in Relation to Host Communities -- Objective indicators of QOL and tourism, P. Laszlo, E. Smeral, R. Perdue -- Destination PLC and QOL of residents, D. Pearce, J. K. Kim, M. Uysal, J. Sirgy -- Tourism development stages and QOL of residents, K. Kim, M. Uysal, J. Sirgy -- Destination competitiveness from the perspectives of providers and QOL, L. Dwyer, G. Crouch, D. Foster -- Perceptions of tourism Impacts and satisfaction with particular life domains (material well-being, emotional well-being, community well-being, and health and safety well-being), K. Kim, X. Li, J. Sirgy, M. Uysal, S. Kruger -- Tourism - recreation conservation and QOL, S. Nicholls, D. Timothy -- Sustainable tourism and QOL, J. Carlsen, T. Tyrrell, E. Turk, D. Weaver -- Economic value of tourism and QOL of residents, L. Dwyer, A.S. Cantallops -- Festivals, events and QOL, L. Jago, G. Moscardo, M. Larson -- Tourism as a revitalization tool of culture and heritage and QOL, J. Liburd, A. Hergesell, L. Jago -- Building social capital to enhance QOL of residents in destinations, C. Jurowski, N. McGehee -- Relationship between lessened / improved QOL and support for tourism, K. Andereck, R. Knopt, C. Vogt -- Different stakeholders in tourism and their perceptions of impacts of tourism on QOL, N. Nickerson, K. Backman -- Impacts of gaming on QOL of residents and types of residents, K. Hsu, W. Roehl -- Tourism development of improvement approaches to enhancing QOL of residents, Allen, T. Var, G. Ozdemir, N. Nickerson -- Community involvement in tourism planning and development and QOL, P. Burns, Lisa Chase, C. Tosun, D. Lund-Durlacher -- Relationship between carrying capacity of destinations and QOL of residents, D. Kerstetter, G. Wall, A. Graefe -- Rural tourism and QOL, P. Long, R. Perdue -- Urban tourism and QOL, G. Ashworth, H. Timmermans, D. Edwards -- Volunteer tourism and QOL, N. McGehee, S. Wearing -- QOL of tourism indicators - development of QOL indicators for tourism, L. Pennington-Gray, Teresa C.H. Tao -- Community tourism & QOL in Hong Kong, Ap Community tourism & QOL in South Carolina: A case study, Backman The effect of tourism on the housing market: the case of Sardinia, B. Blagi, A. Faggian -- Poverty elimination through tourism - QOL, R. Croes, M. Vanegas -- Epilogue: A Synthesis of the QOL Research in Tourism .
Keywords: Quality of life; Well-being.; Tourism; Management; Economic geography; Cultural property; Quality of Life Research; Well-Being.; Tourism Management; Economic Geography; Cultural Heritage